Tiny patients, huge impact: a call to action - Jordee Wells; Anita Shah; Holly Gillis; Sarah Gustafson; Carmin Powell; Amornluck Krasaelap; Samantha Hanna; Jennifer A. Hoefert; Amee Bigelow; Jennifer Sherwin; Emilee C. Lewis; Katherine E. Bline (Frontiers Media S.A., 2024)
The continuation of high-quality care is under threat for the over 70 million children in the United States. Inequities between Medicaid and Medicare payments and the current procedural-based reimbursement model have resulted in the undervaluing of pediatric medical care and lack of prioritization of children's health by institutions. The number of pediatricians, including pediatric subspecialists, and pediatric healthcare centers are declining due to mounting financial obstacles and this crucial healthcare supply is no longer able to keep up with demand. The reasons contributing to these inequities are clear and rational: Medicaid has significantly lower rates of reimbursement compared to Medicare, yet Medicaid covers almost half of children in the United States and creates the natural incentive for medical institutions to prioritize the care of adults. Additionally, certain aspects of children's healthcare are unique from adults and are not adequately covered in the current payment model. The result of decades of devaluing children's healthcare has led to a substantial decrease in the availability of services, medications, and equipment needed to provide healthcare to children across the nation. Fortunately, the solution is just as clear as the problem: we must value the healthcare of children as much as that of adults by increasing Medicaid funding to be on par with Medicare and appreciate the complexities of care beyond procedures. If these changes are not made, the high-quality care for children in the US will continue to decline and increase strain on the overall healthcare system as these children age into adulthood.